2020
DOI: 10.1002/cam4.3186
|View full text |Cite
|
Sign up to set email alerts
|

MYC‐activated lncRNA HNF1A‐AS1 overexpression facilitates glioma progression via cooperating with miR‐32‐5p/SOX4 axis

Abstract: Mounting literatures have revealed the crucial effects of long noncoding RNA (lncRNA) in various cancers, including glioma. HNF1A‐AS1, a novel lncRNA, is reported to modulate tumorigenesis and development of multiple cancers. However, the tumorigenic function of lncRNA HNF1A‐AS1 in glioma remains largely unknown. quantitative reverse transcription and polymerase chain reaction and western blot assays were applied to evaluate the expression of relevant mRNAs and proteins. 5‐Ethynyl‐2’‐ deoxyuridine, terminal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…lncRNAs can regulate the carcinogenic and tumor-suppressive pathways by competitively binding to miR-NAs [11,12] as competing endogenous RNAs (ceRNAs). For example, HNF1A-AS1 is induced by MYC and promotes glioma progression via miR-32-5p/SOX4 [13]. lncRNAARHGAP18 promotes tumor metastasis in hepatocellular carcinoma through miR-153-5p [14].…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs can regulate the carcinogenic and tumor-suppressive pathways by competitively binding to miR-NAs [11,12] as competing endogenous RNAs (ceRNAs). For example, HNF1A-AS1 is induced by MYC and promotes glioma progression via miR-32-5p/SOX4 [13]. lncRNAARHGAP18 promotes tumor metastasis in hepatocellular carcinoma through miR-153-5p [14].…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary nucleus was resuspended in 3 mL 2 M RSB (2 M sucrose, 10 mM Tris-HCl pH 7.4, 10 mM NaCl, 3 mM MgCl 2 , 1 mM DTT, and 0.5 mM PMSF) and centrifuged at 3000 × g for 45 min. The isolated circDLC1 was subjected to RT-qPCR analysis, with U6 and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as nuclear and cytoplasmic controls, respectively [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…MeRIP experiments revealed that after silencing METTL3, the m 6 A level of FAM225A decreased, along with the decreased stability and expression of FAM225A [14]. There have been studies about the pivotal role of HNF1A-AS1 in NSCLC, hepatocellular carcinoma and gastric cancer [15][16][17][18][19]. In CRC, studies have shown that HNF1A-AS1 mainly played biological roles through competitively interacting with microRNAs, such as miR-34a, miR-124 and so on [20,21].…”
Section: Introductionmentioning
confidence: 99%